Predictors of humoral response to recommended vaccines in HIV-infected adults. (October 2017) - Tsachouridou, Olga; Christaki, Eirini; Skoura, Lemonia; Georgiou, Adamantini; Nanoudis, Sideris; Vasdeki, Dimitra; Ntziovara, Maria-Anna; Kotoreni, Georgia; Forozidou, Evropi; Tsoukra, Paraskevi; Germanidis, Georgios; Metallidis, Symeon
Highlights: Antibody responses to the vaccines against hepatitis B, hepatitis A, and S. pneumoniae, in HIV-infected adults were retrospectively assessed. Regarding hepatitis B and hepatitis A, education level and insurance status were the only predictors of response. For S. pneumoniae vaccination, HAART and control of viremia were correlated with better response to vaccination. Abstract: Humoral response to vaccination has been found to be inadequate in individuals infected with the human immunodeficiency virus (HIV). We retrospectively assessed antibody responses to three routinely recommended vaccines, against hepatitis B, hepatitis A and S. pneumoniae, in HIV-infected individuals. Data regarding age at HIV diagnosis, years of infection, sex, nationality, HIV mode of transmission, CD4 cell count, nadir CD4 count, plasma viral load, HIV stage, insurance status, educational level and treatment with Highly Active Antiretroviral Therapy (HAART) were collected. Univariate and multivariate analysis was performed in order to detect factors associated with response to vaccination. 437 patients were assessed for hepatitis B, 627 patients for hepatitis A and 66 patients for S. pneumoniae serologic vaccine responsiveness. Regarding hepatitis B and hepatitis A, education level and insurance status were the only predictors of response. As for S. pneumoniae vaccination HAART and control of viremia were correlated with better response to vaccination.